THE RELATIONSHIP BETWEEN COMMUNICATION SKILLS AND CLINICAL CONFIDENCE AMONG NURSING STUDENTS AT DAI NAM UNIVERSITY IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the status of communication skills and clinical confidence, and to analyze their relationship among nursing students at Dai Nam University in 2025.Methods: A cross-sectional analytical study was conducted on 150 nursing students undergoing clinical practice. Data were collected using a self-administered questionnaire including the safe and effective clinical communications and the nursing cultural competence scale. Data were analyzed using SPSS 26.0 with descriptive statistics, T-test, Pearson correlation, and linear regression.Results: The mean scores of communication skills and clinical confidence were 3.58 ± 0.74 and 3.53 ± 0.78, respectively, indicating moderate levels. Communication skills showed a strong positive correlation with clinical confidence (r = 0.847; p < 0.001). Linear regression analysis indicated that communication skills were a significant predictor of clinical confidence (β = 0.847; p < 0.001), explaining 71.7% of the variance (R² = 0.717).Conclusion: Communication skills are strongly associated with and significantly predict clinical confidence among nursing students. Strengthening communication training in nursing education is essential to improve clinical competence and confidence.
Keywords: Communication skills, clinical confidence, nursing students.